0947 A Randomized Controlled Trial (RCT) Of Prazosin Versus Placebo For Suicidal Posttraumatic Stress Disorder (PTSD) Patients With Nightmares - A Pilot Study. (27th April 2018) - McCall, W V; Youssef, N; Branch, F; Nolla, T; McCloud, L; Moraczewski, J; Tauhidul, L; Phillips, M; Case, D; Rosenquist, P
Abstract: Introduction: Nightmares are a risk factor for suicide, and nightmares are prevalent in PTSD. Prazosin is a standard treatment for nightmares, but has not been tested in suicidal PTSD patients with nightmares. It would be helpful if prazosin mitigated suicidal ideation via nightmare reduction. Methods: Twenty outpatients with PTSD, severe nightmares, and suicidal ideation received escalating doses of prazosin versus matched placebo at bedtime, with weekly escalation of dose for 8 weeks. Patients also took stable doses of SSRIs or SNRIs for comorbid major depressive disorder (N=16), or stable doses of mood stabilizers for comorbid bipolar disorder (N=4). The following were measured weekly: Disturbing Dreams and Nightmare Severity Index (DDNSI), Insomnia Severity Index (ISI), Scale for Suicide Ideation (SSI), Hamilton Rating Scale for Depression (HRSD), PTSD Check List (PCL), and vital signs. Data were analyzed by constrained longitudinal mixed models. Results: Participants included 17 women and 3 men, with a mean age of 39.8 +/- 14.5. Participants were moderately suicidal at baseline, and the combined sample showed significant improvement to 'mild' suicidality by the end of the study. There was no difference in SSI scores between groups. Likewise, PCL scores declined over time, but with no differences between treatment groups. There was no change in vital signs over time, or between groups. While DDNSI scores, ISI scores, and HRSD scores all showed improvement over time for the entire sample, remarkably, the prazosin groups showed significantly less improvement than the placebo group for all three variables. There were no suicide attempts, but one patient in the placebo group required emergent psychiatric hospitalization. There were four episodes of weakness or fainting, including three in the prazosin group, and one in the placebo group. Conclusion: In this small pilot study of suicidal PTSD patients with nightmares, prazosin was associated with worse outcomes for nightmares, insomnia, and depression scores as compared with placebo. There was no effect on suicidality. These surprising results require replication. Support (If Any): American Foundation for Suicide Prevention.